2020
DOI: 10.1200/jco.2020.38.15_suppl.12011
|View full text |Cite
|
Sign up to set email alerts
|

Integrated geriatric assessment and treatment (INTEGERATE) in older people with cancer planned for systemic anticancer therapy.

Abstract: 12011 Background: Older people experience significant adverse effects of cancer and anti-cancer therapy due to age-related vulnerabilities, including medical, functional, cognitive, nutritional and psychosocial issues. Comprehensive geriatric assessment and management (CGAM) provides a powerful framework to assess an older person’s health status and offers a coordinated, person-centered approach to care. Despite its effectiveness, the uptake of CGAM in oncology has been limited due to a lack of randomized evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 0 publications
1
98
0
Order By: Relevance
“…A comprehensive geriatric assessment can help achieve the required balance between treatment benefits and side-effects and is recommended by guidelines from the American Society of Clinical Oncology, the National Comprehensive Cancer Network, and the International Society for Geriatric Oncology [ 28 , 40 ]. In a randomised study, integrated oncogeriatric care has recently been shown to improve QoL in older patients with cancer being considered for systemic anticancer therapy [ 41 ]. Of particular interest was our finding that in patients ≥80 the negative impact on QoL does not resolve, which suggests a lack of resilience in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive geriatric assessment can help achieve the required balance between treatment benefits and side-effects and is recommended by guidelines from the American Society of Clinical Oncology, the National Comprehensive Cancer Network, and the International Society for Geriatric Oncology [ 28 , 40 ]. In a randomised study, integrated oncogeriatric care has recently been shown to improve QoL in older patients with cancer being considered for systemic anticancer therapy [ 41 ]. Of particular interest was our finding that in patients ≥80 the negative impact on QoL does not resolve, which suggests a lack of resilience in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Although GA‐guided interventions are effective for improving survival and functional status in several scenarios [2], there is a lack of information regarding the effects of GA‐guided care on traditional “hard” oncological outcomes, such as overall survival (OS), treatment toxicity, or quality of life (QoL) [3]. Fortunately, four randomized clinical trials (RCT) presented at the 2020 ASCO Annual Meeting have provided new evidence showing that the implementation of GA‐guided interventions for older adults with cancer can in fact lead to improvements in QoL and decreased treatment toxicity, without compromising survival (Table 1) [ 4–6]. These RCTs represent a giant leap forward for geriatric oncology, because they provide a strong foundation that will allow for GA‐guided interventions to become the standard of care for all older adults with cancer.…”
Section: Figurementioning
confidence: 99%
“…The third trial was INTEGERATE, which investigated the effect of geriatrician‐oncologist comanagement on the QoL of older adults with solid tumors or lymphoma starting a new treatment line (including targeted therapy) [6]. Patients aged ≥70 years treated at three Australian hospitals were randomized in a 1:1 fashion to an integrated onco‐geriatric care intervention or to usual care.…”
Section: Figurementioning
confidence: 99%
“…Until recently, no randomized trial had yet to demonstrate that GA-guided care interventions definitively improve outcomes in older adults with cancer, despite these interventions improving outcomes in older non-cancer populations [45] . However, at the 2020 ASCO virtual meeting, 3 randomized trials were presented and demonstrated GA-based interventions helped improve quality of life and toxicity rates among older adults receiving systemic therapy without decreasing expected survival [27] , [46] , [47] . Additionally, to help clinicians better identify frailty, a frailty index (scoring system) generated from the results of GA has been designed that is predictive of all-cause mortality, reduced health-related quality of life, and hospitalizations [48] , [49] , [50] .…”
Section: Geriatric Assessmentmentioning
confidence: 99%